+0  
 
0
349
2
avatar

3xy((y²/3x²)-(5y/2x²)+(3/x))=?

 12.01.2017

Beste Antwort 

 #1
avatar+10377 
+10

3xy((y²/3x²)-(5y/2x²)+(3/x))=?

 

laugh

 12.01.2017
 #1
avatar+10377 
+10
Beste Antwort

3xy((y²/3x²)-(5y/2x²)+(3/x))=?

 

laugh

Omi67 12.01.2017
 #2
avatar+8251 
+5

3xy((y²/3x²)-(5y/2x²)+(3/x))=?

 

\(\large 3xy((\frac{y^2}{3x^2} )-(\frac{5y}{2x^2} )+(\frac{3}{x} ))\)

 

\(\large =\frac{3xy(2y^2-15y+8x)}{6x^2} \)

 

\(\large=\frac{6xy^3-45xy^2+24x^2y}{6x^2} \)  \3x

 

\(\large=\frac{2y^3-15y^2+8xy}{2x}\)

 

\(\large=\frac{y}{2x}\times(2y^2-15y+8x)\)

 

laugh  !

 12.01.2017

9 Benutzer online